Saudi Arabia's Efforts in Implementing Saudi Vision 2030 - Fardien Faiz Syaputra; Haryo Prasodjo (Universitas Teuku Umar, 2023)
Saudi Arabia is a country that is quite rich in oil production. But within a few years of peaking at the top, world oil prices have declined, which has seen Saudi Arabia drop below the United States. The government of Saudi Arabia then responded to the decline in the economy caused by fluctuating oil prices by compiling the Arab Vision 2030. The goal of the Arab Vision 2030 is to diversify the economy or want to release Saudi Arabia's economic dependence on oil production. This study seeks to analyze the efforts made by Saudi Arabia in implementing the Arab Vision 2030. This issue is more focused on the efforts that have been planned and will be carried out. This study uses the concept of national interest to analyze Saudi Arabia's efforts to implement Saudi Vision 2030. This research was conducted using a qualitative method with a literature study and case study approach. The data was collected through primary and secondary data in the form of articles, journals, and news in the mass media. This study concludes that several efforts made by Saudi Arabia began with new, more liberal policies and the creation of several infrastructures that support Saudi Arabia's economic diversification. Saudi Arabia is trying to increase its economy through the non-oil and gas sectors. Muhammad bin Salman, the Crown Prince, has a very important role in making policies related to economic diversification in Saudi Arabia. The efforts can still be seen from various aspects, such as increasing Saudi Arabia's investment in several countries and changing patterns of economic development in the non-oil and gas sector